Virus entry and its inhibition to prevent and treat hepatitis B and hepatitis D virus infections - Tu, Thomas; Urban, Stephan (Current opinion in virology, 2018)
While chronic infection with the human hepatitis B virus (HBV) and hepatitis delta virus (HDV) inflict major health burdens worldwide, current therapies cannot cure patients. One possible novel approach is blocking virus entry to prevent the establishment of infection in naïve hepatocytes. As HBV and HDV use identical viral envelope proteins and the same entry mechanisms, such a strategy would target both viruses. Entry inhibitors (e.g. neutralizing antibodies) have been relegated to the limited role of prophylaxis. However, recent clinical data and infection studies show that new viral entry inhibitors could play a major role in eliminating intrahepatic HBV/HDV genomes. We highlight the consequences on viral persistence after preventing virus entry and the therapeutic benefits entry inhibitors could achieve.